Demographic and epidemiological characteristics of HIV opportunistic Infections among older adults in Nigeria (2017)
Background: In view of the maturing HIV epidemic in sub-Saharan Africa, better understanding of its epidemiology among older adults is necessary in order to design appropriate care and treatment programmes for them. Objectives: To describe the demographic and epidemiological characteristics of HIV opportunistic infections among newly enrolled patients aged 50 years and above in Ibadan, South-West Nigeria. Methods: Analysis of data extracted from electronic records of 17, 312 subjects enrolled for HIV/AIDS care and treatment between January 2006 and December 2014 at the ART clinic, University College Hospital, Ibadan. Results: Age of the patients ranged from 18 to 90 years with a mean of 36.4 years (SD= 10.3) with older adults constituting 12.0% (2075). Among older adults, about half (52.9%) were females. Majority (59.1%) were currently married while 25.9% were widowed. Prevalence of opportunistic infections was 46.6%. The commonest opportunistic infections (OIs) were: oral candidiasis (27.6%), chronic diarrhoea (23.5% and peripheral neuropathy (14.8%). Significant factors associated with opportunistic infections in older adults were: CD4 count less than 350 (OR=3.12, CI: 2.29-4.25) and hepatitis C virus co-infection (OR=2.17, CI: 1.14-4.13). Conclusion: There is need for prompt response to the peculiar challenges associated with the emerging shift in the epidemiology of HIV and associated infections in sub-Saharan Africa.